PENGARUH KULIT PISANG KEPOK(Musa paradisiacaformatypica) DAN DAUN PEPAYA (Carica papaya L.) TERHADAP KUALITAS NUTRISI PAKAN KELINCI BERBENTUK PELET - Sri Rohani Rohani; Ahmad Tohardi; Duta Setiawan (Fakultas Pertanian Universitas Tanjungpura, 2019)
Feed is one of the most important factors for the success of a livestock business.Rabbit’s growth can be optimal when the amount as well as the quality of the feed, and the nutrient is fulfilled decently. This study aims to determine the nutritional quality of rabbit feed that is in the form of pelet combined with musa paradisiacal formatypica and carica papaya. This study had been conducted for 3 months (March - June 2018) at the laboratory of Teknologi Hasil Pertaniandan Kesuburan Tanah, agriculture department, Universitas Tanjungpura Pontianak. This study used randomized block design which are 5treatments and 5 repetitions; P1 (24% of Banana peel+ 0 % Papay leaves), P2 (18% Banana peel + 6 Papay leaves), P3 (12% Banana peel + 12 Papay leaves), P4 (6% Banana peel + 18% Papay leaves) and P5 (0% Banana peel + 24% Papay leaves). The analysis showsthat the treatment has significant effect (P<0,05) on moisture, ash, crude fat, crude protein, crude fibre and carbohydrates. The results of this study concluded that the value of the nutritional content in accordance with the needs of rabbits was obtained in treatment 4, namely 6% kepok banana peel and 18% papaya leaves. Based on the nutritional content produced, the feed can be given to adult rabbits.Keywords: Banana Peel, Papay Leaves, Proximate Analysis, Pellets